Justyna (Euphemia) Szaniawska – Abbess of the Nesvizh Benedictine Monastery in the 18th Century - Pietrzak, Jarosław (History / Istorija, 2025)
The work presents the figure of a unique abbess of the Benedictine monastery in Nesvizh – Euphemia Szaniawska. During her tenure from 1758 to 1799, the abbess had to face a number of problems, including disputes over monastic property, serfs and pledges. Regardless, she was an efficient organiser. As a result, this allowed for the expansion of the monastery buildings, renovation works and the foundation of new temples. The work also shows the abbess’s relationship with her protectors – the Radziwiłł princes, which was related to the existence of the monastery and even its reaction to the most important political events at the end of the Polish-Lithuanian Commonwealth.